Gestational Diabetes Mellitus Does Not Change the Pharmacokinetics and Transplacental Distribution of Fluoxetine and Norfluoxetine Enantiomers - Daniela Miarelli Carvalho; Glauco Henrique Balthazar Nardotto; Gabriela Campos de Oliveira Filgueira; Geraldo Duarte; Ricardo Carvalho Cavalli; Vera Lucia Lanchote; Elaine Christine Dantas Moisés (Pharmaceutics)
Background/Objectives: Fluoxetine (FLX) is the inhibitor of serotonin reuptake most prescribed in pregnant women with depression. This study evaluates the influence of gestational diabetes mellitus (GDM) on the enantioselective pharmacokinetics and transplacental distribution of FLX and its metabolite norfluoxetine (norFLX). Methods: Ten pregnant women diagnosed with GDM (GDM group) were investigated in the third trimester of gestation after they achieved good glycemic control. They received a single oral dose of 20 mg FLX, and blood samples were collected from 0 to 672 h. On the day of delivery, after another single oral dose of 20 mg FLX, blood samples of maternal vein, umbilical vessels and intervillous space were collected at birth. The pharmacokinetics parameters obtained for pregnant women diagnosed with GDM were compared with a group of healthy pregnant women (n = 9) previously investigated using Kruskal–Wallis’s rank-sum test with the Dunn–Bonferroni post hoc test. Results: The area under the plasma over time curve (AUC0–∞) were 197.93 and 109.62 ng∙h/mL for FLX and 600.39 and 960.83 ng∙h/mL for norFLX, respectively, for their R-(+)- and S-(-)- enantiomers. The umbilical vein/maternal vein ratio for FLX and norFLX enantiomers was nearly 0.3, inferring low placental transfer. The umbilical artery/umbilical vein ratios were nearly 0.7 for both FLX and norFLX enantiomers, indicating absence or small fetal metabolism. Conclusions: The GDM did not alter the pharmacokinetics of FLX and norFLX enantiomers in patients with good glycemic control evaluated in the third trimester of gestation.